Psychological distress in Nepalese residents during COVID-19 pandemic: a community level survey - Dhan Bahadur Shrestha; Bikash Bikram Thapa; Nagendra Katuwal; Bikal Shrestha; Chiranjibi Pant; Bina Basnet; Pankaj Mandal; Amol Gurung; Ankita Agrawal; Ramhari Rouniyar (BMC Psychiatry, 2020)
Abstract Background COVID-19 pandemic has created unprecedented health and economic impact. Psychological stress, anxiety and depression are affecting not only COVID-19 patients but also health professionals, and general population. Fear of contracting COVID-19, forced restrictive social measures, and economic hardship are causing mental trauma. Nepal is a developing country from South Asia where the COVID-19 pandemic is still evolving. This online survey has been carried out to understand impact of COVID- 19 on mental health of Nepalese community dwellers. Methods The COVID-19 Peritraumatic Distress Index (CPDI) questionnaire adapted from the Shanghai Mental Health Centre was used for online data collection from 11 April-17 May 2020. Collected data were extracted to Microsoft excel-13 and imported and analyzed using SPSS (Statistical Package for Social Sciences) version-22. An initial univariate analysis was conducted for all variables to assess the distribution. Logistic regression analyses were done to estimate the odds ratios of relevant predicting variables. Results A total of 410 participants completed the self-rated questionnaires. Mean age of study participants was 34.8 ± 11.7 years with male preponderance. 88.5% of the respondents were not in distress (score less than 28) while, 11% had mild to moderate distress and 0.5% had severe distress. The prevalence of distress is higher among age group > 45 years, female gender, and post-secondary education group. Health professional were more likely to get distressed. Respondents with post-secondary education had higher odds (OR = 3.32; p = 0.020) of developing distress as compared to respondents with secondary education or lower. Conclusion There is lower rate of psychological distress in city dwellers and people with low education. Adequate intervention and evaluation into mental health awareness, and psychosocial support focused primarily on health care workers, female and elderly individuals is necessary.